2017
DOI: 10.1590/1981-22562017020.160163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characterization of patients receiving home care in the city of Maceió, in the state of Alagoas, Brazil

Abstract: Objective: To clinically and epidemiologically characterize patients receiving home care in the city of Maceio, in the state of Alagoas, Brazil. Methods: An observational, crosssectional study with a sample of 859 patients was carried out, based on data obtained from the medical records of institutions that provide a home care service. A total of 445 patients were from a public service and 414 were from a private service. Descriptive analysis was used for the demographic, clinical and functional variables. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
1
22

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 18 publications
7
8
1
22
Order By: Relevance
“…The results of the present study revealed that strokes were most common, which corroborates the findings of other studies conducted in Brazil 18,19,22 and elsewhere according to Baumann et al (2014) 23 . Importantly, stroke survivors are often unable to perform routine activities and suffer communication (e.g., language, writing, and speaking) and body mobility disorders.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of the present study revealed that strokes were most common, which corroborates the findings of other studies conducted in Brazil 18,19,22 and elsewhere according to Baumann et al (2014) 23 . Importantly, stroke survivors are often unable to perform routine activities and suffer communication (e.g., language, writing, and speaking) and body mobility disorders.…”
Section: Discussionsupporting
confidence: 93%
“…prevalent even after the onset of morbidities such as stroke and cerebral palsy, which were the most prevalent forms found in this study. This result has also been found by other studies 23,24 , but future studies should evaluate the degree of disease severityto facilitate response and improvement in particular situations where oral feeding remains limited.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This adaptation possibly implies a decrease in quality of life. 23 Functional capacity among elderly people Mota TA, Alves MB, Silva VA, Oliveira FA, Brito PMC, Silva RS Other variables such as gender, marital status and schooling level did not present a significant association for the development of dependence among elderly people, although some studies present statistically significant associations between these variables and functional capacity.…”
Section: Discussionmentioning
confidence: 90%
“…O SAD atende pacientes predominantemente idosos, com multimorbidades e altas taxas de restrição ao leito e de dependência. 10 Por isso, há uma íntima relação entre cuidados paliativos, cuidados domiciliares e a população idosa, tornando-se importante avaliar o prognóstico nesse contexto.…”
Section: Introductionunclassified